Peran Biaya Operasional Dan Pendapatan Operasional Dalam Hubungan Pembiayaan Dengan Return On Asset Pada Bank Umum Syariah Di Indonesia - Linda Devy Ramadhani; Taufikur Rahman (LPPM ISNJ Bengkalis, 2021)
This study aims to analyze the effect of mudharabah financing, murabahah financing, and ijarah financing on return on assets (ROA) with operating costs and operating income (BOPO) as intervening variables. This research is quantitative research using secondary data in panel data with a purposive sampling technique. The sample used is three Islamic commercial banks registered with the financial services authority from 2017 to 2020. Data analysis includes descriptive test, stationary test, regression test, classical assumption test, path analysis test, and Sobel test. The results of this study indicate that mudharabah financing and ijarah financing do not affect ROA. Murabahah and BOPO financing has negative and significant effects on ROA. BOPO did not mediate the effect of mudharabah, murabahah, and ijarah financing on ROA.